Study of the binding of copper (II) ions to the heavy chain of silk fibroin using the charmm22 force field - Polvonova , Gulinur; Eshchanov, Khushnudbek; Esomurodova , Risolat (International Journal of Advanced Chemistry, 2024)
Silk fibroin is of great interest due to its unique mechanical properties and preparation of biomaterials. It is important to study the mechanisms of the interaction of fibroin with metal ions and the composition of the resulting complexes. We studied the possibilities of coordination binding of copper (II) ions to the heavy chain of the silk fibroin molecule of calculations using the CHARMM22 force field and determined the optimal parts for coordination bonds. To practically confirm the results obtained in theoretical calculations, samples of fibroin containing copper (II) ions were analyzed by ATR-FTIR spectroscopy, and it was proved that copper ions are coordinately bound to the groups in fibroin. The agreement of the results obtained in the theoretical calculations with the results of the actual analysis confirms that indeed, copper (II) ions correspond to the conditions studied by modelling.